Performance Assessment of Construction Engineering and Management (CEM) Degree Program in Developing Countries: Case of Pakistan. Issue 1 (2nd January 2017) - Naveed, Mian Hassan; Thaheem, Muhammad Jamaluddin; Khurshid, Muhammad Bilal; Farooqui, Rizwan Ul Haque
ABSTRACT: The performance of construction industry is largely supported by the competence and skills generated by Construction Engineering and Management (CEM) programs offered in the country. A review of published literature points to scarcity of studies evaluating performance of curricula with respect to generating the requisite skills. In an attempt to assess the efficiency of CEM programs offered in Pakistan, this study identifies the key knowledge areas, technical skills, and expertise that these programs need to focus on for sufficiently preparing the post graduating students entering modern and complex construction industry. In doing so, two universities (NEDUET and NUST) offering mature CEM program at postgraduate level have been engaged. Based on a questionnaire survey of CEM graduates, employers and academicians, it is found that the program content is adequately designed and delivered by well versed and competent instructors. Generally, a high degree of agreement for technical skills is found among the perceptions of graduates and the expectations of the industry. However, some major challenges are identified which if addressed can help boost the satisfaction level of students. Acknowledging the possibility for improvement, recommendations for curricula updates in order to bridge the gap between academia and industry are proposed.